2006
DOI: 10.1063/1.2337385
|View full text |Cite
|
Sign up to set email alerts
|

High open-circuit voltage values on fine-grained thin-film polysilicon solar cells

Abstract: Grain boundaries are known to be the main limiting factor for a high performance of polysilicon solar cells. Defects at these grain boundaries serve as recombination centers for minority and majority carriers. Grain boundaries are also known to be paths for enhanced hydrogen diffusion, which results in passivation of part of the defects. In this paper, we show that grain boundaries are also paths for an enhanced phosphorus diffusion that limits the effect of hydrogen passivation. Phosphorus spikes along the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 19 publications
2
16
0
2
Order By: Relevance
“…In general we observe that the D-concentration in the layer is larger than the defect density of our layers which is around 10 18 cm -3 [5]. Johnson et al also showed a much larger D (factor of thousand difference) concentration than the number of dangling bonds for polysilicon [6].…”
Section: P-type Layer Characterizationsupporting
confidence: 42%
“…In general we observe that the D-concentration in the layer is larger than the defect density of our layers which is around 10 18 cm -3 [5]. Johnson et al also showed a much larger D (factor of thousand difference) concentration than the number of dangling bonds for polysilicon [6].…”
Section: P-type Layer Characterizationsupporting
confidence: 42%
“…The deposition was done using high-temperature chemical vapour deposition (CVD) at temperatures around 1130°C and at atmospheric pressure using trichlorosilane as a precursor gas. The thickness of the p + p-type layers was between 1 and 6 µm and the grain size of the material was typically around 0.2 µm [4]. After the growth of the polysilicon layers, the layers were textured in a plasma texturing setup or using a wet treatment in an acidic ('poly-etch') solution.…”
Section: Methodsmentioning
confidence: 99%
“…The improvement of the V oc after texturing is because of the thinner p-type layer, and is discussed in more detail in Ref. [4]. On the other hand, growing a thinner p-type layer has no influence on the J sc .…”
Section: Texturing Of Fine-grained Polysilicon Layersmentioning
confidence: 95%
“…In both cases the same patterns as after defect etching were found, showing that the crystallographic IGD have a strong recombination activity. This is a consequence of the emitter diffusion which results in deep emitter spikes at grain boundaries due to enhanced diffusion of phosphorus along these grain boundaries [5]. both grains of Figure 3d is a consequence of a different rotation around the [100] axes of both (100) grains.…”
Section: Room Temperature Ebicmentioning
confidence: 99%